1984
DOI: 10.1016/0014-5793(84)81001-7
|View full text |Cite
|
Sign up to set email alerts
|

pp60c‐src is a substrate for phosphorylation when cells are stimulated to enter cycle

Abstract: The endogenous cellular oncogene products, pp60 c‐src , exhibits a protein kinase activity, but is itself a phosphoprotein. Based on the assumption that pp60 c‐src might play a role in the control of cell proliferation, we have studied its behaviour as a substrate for phosphorylation known to occur when quiescent, serum‐deprived cells are stimulated to enter cell cycle following addition of either serum, platelet‐derived growth factor or the phorbol ester derivative, 12‐0‐tetradecanoyl‐phorbol‐13‐acetate. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The scraped cytoskeletons were homogeneized with 12 strokes in a tight-fitting Dounce homogeneizer followed by centrifugation at 100000 x g for 1 h. The supernatant ( z 14 ml at 1 -1.2 mg/ml) was applied to a DEAE-cellulose column ( z 4 cm3) equilibrated with buffer D (20 mM Tris/HCl, pH 7.5, 0.5 mM EGTA, 0.5 mM EDTA, 10 mM 2-mercaptoethanol, 1 mM PhMeS02F). Preliminary experiments had shown that the peak of pp60"-"'" and pp60'-"'" activity eluted slightly below 0.1 M NaC1, as reported also by others [22]. Therefore, in order to achieve as concentrated preparations as possible, the fractions enriched in pp60"-"'" or in pp60"-"" were obtained by a one-step elution with 0.15 M NaCl in buffer D and collecting the proteins that eluted at the highest absorbance.…”
Section: Cells Viruses and Antibodiessupporting
confidence: 81%
See 1 more Smart Citation
“…The scraped cytoskeletons were homogeneized with 12 strokes in a tight-fitting Dounce homogeneizer followed by centrifugation at 100000 x g for 1 h. The supernatant ( z 14 ml at 1 -1.2 mg/ml) was applied to a DEAE-cellulose column ( z 4 cm3) equilibrated with buffer D (20 mM Tris/HCl, pH 7.5, 0.5 mM EGTA, 0.5 mM EDTA, 10 mM 2-mercaptoethanol, 1 mM PhMeS02F). Preliminary experiments had shown that the peak of pp60"-"'" and pp60'-"'" activity eluted slightly below 0.1 M NaC1, as reported also by others [22]. Therefore, in order to achieve as concentrated preparations as possible, the fractions enriched in pp60"-"'" or in pp60"-"" were obtained by a one-step elution with 0.15 M NaCl in buffer D and collecting the proteins that eluted at the highest absorbance.…”
Section: Cells Viruses and Antibodiessupporting
confidence: 81%
“…The protein concentration of these fractions was generally around 0.5 mg/ml and their average NaCl concentration was 70 mM. An enrichment of approximately 20-fold in pp60"-"" and pp60'-"'" activities was achieved at that stage, as determined by measurement of TBRIgG phosphorylation [22].…”
Section: Cells Viruses and Antibodiesmentioning
confidence: 98%
“…We (29) and others (26,62) have shown that pp60c src is phosphorylated rapidly and stoichiometrically at a normally unphosphorylated serine(s) when cells are treated with tumor promoters that bind and activate protein kinase C. The same sites, serine 12 (S12) in mammalian pp6Ocsrc and both S12 and serine 48 in chicken pp6fc-src, can be phosphorylated by purified protein kinase C in vitro (29). In this report, * Corresponding author. we demonstrate that all agonists of phosphatidylinositol turnover, which we have tested in fibroblasts, lead to the near stoichiometric phosphorylation at S12.…”
mentioning
confidence: 69%
“…Like its viral counterpart, the cellular src protein belongs to the tyrosine protein kinase family (review in Jove and Hanafusa, 1987). Biochemical studies have taken advantage of this property and have provided information on pp60~-s'~: the cellular src protein preferentially associates with plasma membranes, like pp60 .... , although, contrary to pp60 v-'~, such an interaction does not appear to occur via the non-ionic, detergent-insoluble cellular matrix (Loeb et al, 1987;Hamaguchi and Hanafusa, 1987); pp60 ~-'~ has been detected in intracellular membranes associated with the nuclear envelope, like pp60 ~-sr~ (Resh and Erikson, 1985) and with more specific structures such as chromaffin granules (Parsons and Greutz, 1986) and synaptic vesicles (Barnekow et al, 1990); platelets have also been shown to contain a relatively high level of pp60 ..... (Rendu et al, 1989;Ferrell et al, 1990); the cellular protein does not seem to form a soluble cytoplasmic complex with two cellular proteins, contrary to pp60 v-s' (Tamura et al, 1984).…”
mentioning
confidence: 99%